Dakwah Hamka Menjawab Isu-Isu Kenegaraan dalam Tafsir Al-Azhar - Akmal Rizki Gunawan Hasibuan; Agustina Agustina (TSAQAFAH, 2019)
AbstractThis explained that Buya Hamka was an Indonesian interpreter who had a major influence on efforts in grounding state values. This paper confirms that the discourse on state issues in al-Azhar's interpretation delivered by Hamka has a selective and accommodating impression. For example, in the context of religious and state relations, he was more inclined to Husein Muhammad Haikal's opinion which is said that in Islam there is a set of principles, moral and ethical values related to the life of society and the state. Whereas in its implementation, Islam does not determine the standard system of government, but Islam has the right to determine the system to be used. As for the state ideology, there were found inconsistencies in Hamka's thinking, a kind of development or shift in Hamka's attitude. On the one hand, Hamka wants an ideology of Islam in Indonesia, while on the other hand, he recognizes Pancasila as a state ideology. It is not another due in around the fifties, Muslims suspected with so many interpretations and differences of interpretation concerning the Pancasila as the State ideology, moreover, the interpretation of the secular group. The approach used in this study is an interpretive approach in order to understand a figure's thoughts/interpreters through their works.Keywords: Hamka, State Issues, Al-Azhar Interpretation.AbstrakIni memaparkan bahwa Buya Hamka (1908-1981) adalah salah seorang tokoh tafsir Indonesia yang punya pengaruh besar terhadap upaya pembumian nilai-nilai kenegaraan. Tulisan ini menegaskan bahwa wacana isu-isu kenegaraan dalam tafsir al-Azhar yang disampaikan oleh Hamka kepada para pembaca tafsirnya memiliki kesan selektif dan  akomodatif. Seperti misalnya, konteks hubungan agama dan negara, Hamka lebih cenderung kepada pendapat Muhammad Husein Haikal, yang mana dikatakan bahwa dalam Islam terdapat seperangkat prinsip dan tata nilai moral serta etika yang berkaitan dengan kehidupan bermasyarakat dan bernegara. Sedangkan  dalam pelaksanaannya, Islam tidak menentukan sistem pemerintahan baku, akan tetapi Islam berhak menentukan sistem yang akan digunakan. Adapun mengenai ideologi negara, ditemukan adanya inkonsistensi dalam pemikiran Hamka, semacam perkembangan atau pergeseran sikap Hamka. Di satu sisi Hamka menginginkan Indonesia berideologi Islam, sedangkan disisi lain ia mengakui Pancasila sebagai ideologi negara. Hal tersebut tidak lain dikarenakan pada sekitar tahun lima puluhan, umat Islam curiga dengan banyaknya penafsiran dan perbedaan penafsiran mengenai Pancasila sebagai ideologi negara, terlebih lagi penafsiran dari kelompok sekuler. Adapun pendekatan yang digunakan dalam studi ini adalah pendekatan interpretasi (interpretatif approach) dalam rangka memahami pemikiran seorang tokoh/mufasir melalui karya-karyanya.Kata Kunci: Hamka, Isu-Isu Kenegaraan, Tafsir Al-Azhar.